Potentially predictive factors for hearing function improvement in pediatric cytomegalovirus infection therapy - Agung Triono; Elisabeth Siti Herini; Braghmandita Widya; Dian Kesumapramudya Nurputra (Paediatrica Indonesiana, 2021)
Background Symptomatic congenital cytomegalovirus (CMV) infection has an impact mainly on neurological sequelae, including sensorineural deafness. Because of the long-term impact, early treatment of CMV infection is mandatory. However, predictive factors for hearing function improvement in CMV infection therapy remain unexamined. Objective To evaluate potential predictive factors for hearing improvement in pediatric CMV infection therapy. Methods All medical record data of patients aged 0-6 years with CMV infection who completed a 6-week course of ganciclovir therapy or a combination of a 4-week course of ganciclovir and a 2-week course valganciclovir from January 2013 to December 2017 were collected. Age at onset of therapy, gender, gestational age, nutritional status, multi-organ involvement, and neurological symptoms were studied as potential predictive factors of hearing improvement in CMV therapy. The effectiveness of CMV infection therapy on improving hearing function was measured with the brainstem evoked response audiometry (BERA) test. Results BERA tests proportion in the right, left, and best ear showed significant improvement after therapy. All variables analyzed were not statistically significant as predictive factors for hearing improvement in CMV infection therapy. Conclusion Ganciclovir/valganciclovir therapy in CMV infection patients accounted for the improvement of hearing impairment. However, none of the assessed factors were considered predictive for improving hearing function in CMV infection therapy.